The Implementation of Islamic Education in the Guidance of Converts Muallaf in East Yapen District - Suwandi; Syamsuddin; Yahdi, Muh. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to determine the Islamic education development program, the implementation of Islamic education, and the obstacles in the process of implementing Islamic education through the Islamic development program for converts in East Yapen District, Yapen Islands Regency. This research uses a qualitative method with a case study approach. Data were collected through participant observation, semi structured interviews, and documentation. The research instruments included partisipant observation, interview, and documentation. Data were analyzed using the Miles and Huberman interactive model, which include data reduction, data display, conclusion drawing, and verification. The validity was carried out using data triangulation tests. The results of this study found that the Islamic education development program for converts in East Yapen District had been implemented through various activities such as religious studies, reading and writing the Qur’an, practicing worship, and so on. This program is able to provide understanding for converts regarding Islamic education, not only as an addition to religious knowledge, but as practical guidance that helps them adapt to the demands of Islamic teachings in their daily lives. The implementation of Islamic education for converts in East Yapen District takes place through an adaptive and gradual approach according to the social, psychological conditions and level of understanding of the converts. The obstacles that occurred in the process of implementing Islamic religious education through a coaching program for converts in East Yapen District that were found in this study were the lack of preachers and mentors and limited time and work schedules. Abstrak: Penelitian ini bertujuan untuk mengetahui program pembinaan pendidikan Islam, penerapan pendidikan Islam, dan hambatan-hambatan dalam proses penerapan pendidikan Islam melalui program pembinaan Islam pada para muallaf di Distrik Yapen Timur, Kab. Kepulauan Yapen. Penelitian ini menggunakan metode kualitatif dengan jenis studi kasus. Metode pengumpulan data dilakukan melalui observasi partisipatif, wawancara, dan dokumentasi. Instrumen penelitian ini terdiri dari observasi partisipatif, wawancara, dan dokumentasi. Data dianalisis menggunakan model interaktif Miles dan Huberman, melalui reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Validitas dilakukan menggunakan uji triangulasi data. Hasil penelitian ini ditemukan bahwa program pembinaan pendidikan Islam bagi para muallaf di Distrik Yapen Timur telah dilaksanakan dengan berbagai kegiatan seperti pengajian, baca tulis Al-Qur’an, praktik ibadah, dan sebagainya. Program tersebut mampu memberikan pemahaman bagi muallaf mengenai pendidikan Islam bukan hanya sebatas penambahan pengetahuan keagamaan, tetapi sebagai bimbingan praktis yang membantu mereka menyesuaikan diri dengan tuntunan ajaran Islam dalam kehidupan sehari-hari. Penerapan pendidikan islam pada para muallaf di Distrik Yapen Timur berlangsung melalui pendekatan yang adaptif dan bertahap sesuai dengan kondisi sosial, psikologis, dan tingkat pemahaman muallaf. Hambatan yang terjadi dalam proses penerapan pendidikan agama islam melalui program pembinaan pada para muallaf di Distrik Yapen Timur yang ditemukan dalam penelitian ini adalah Kurangnya mubalig dan pembina dan Keterbatasan waktu dan kesibukan kerja.